2015
DOI: 10.1097/rct.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dynamic Phase Enhancement of Hepatocellular Carcinoma Using Gadoxetate Disodium vs Gadobenate Dimeglumine

Abstract: PURPOSETo determine the differences in enhancement pattern of hepatocellular carcinoma (HCC) during first 5 minutes of post-contrast phases MRI with gadoxetic acid (Gd-EOB-DTPA) versus gadobenate dimeglumine (Gd-BOPTA) using the FDA approved doses. METHODS AND MATERIALS95 patients with HCC were examined on 1.5 T scanner; 74 patients with Gd-BOPTA and 21 with Gd-EOB-DTPA. Using the same MRI parameters, post-contrast imaging was performed at pre-contrast, arterial, portal venous, equilibrium, and 5 minute delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…In addition to a lower administered volume, the lower approved gadolinium dose may lead to reduced peak enhancement of the organs on the AP and PVP compared with other agents . Similarly, peak enhancement of HCC may be diminished: in one study, there was a tendency toward a lower contrast‐to‐noise ratio of HCC on the AP with gadoxetate compared with gadobenate, although the difference was not statistically significant …”
Section: Potential Pitfalls Of Gadoxetate Mrimentioning
confidence: 98%
See 3 more Smart Citations
“…In addition to a lower administered volume, the lower approved gadolinium dose may lead to reduced peak enhancement of the organs on the AP and PVP compared with other agents . Similarly, peak enhancement of HCC may be diminished: in one study, there was a tendency toward a lower contrast‐to‐noise ratio of HCC on the AP with gadoxetate compared with gadobenate, although the difference was not statistically significant …”
Section: Potential Pitfalls Of Gadoxetate Mrimentioning
confidence: 98%
“…Imaging in the HBP is a major advantage of gadoxetate. By achieving high signal‐to‐noise and contrast‐to‐noise ratios, the HBP may show HCC with higher conspicuity than other sequences . Some lesions detected in the HBP are identified and characterized in retrospect on other sequences …”
Section: Potential Advantages Of Gadoxetatementioning
confidence: 99%
See 2 more Smart Citations
“…The effects of the small administered volume and gadolinium content are reflected in the weak arterial enhancement on images ( 6 7 ) and can pose challenges to capturing optimal arterial-phase imaging ( 10 ). Recent studies revealed that weak arterial enhancement can possibly affect the lesion conspicuity of hypervascular tumors such as HCCs and focal nodular hyperplasias during the arterial phase of gadoxetate-enhanced liver MR imaging in comparison with gadobenate dimeglumine-enhanced MR imaging ( 17 18 ).…”
Section: Challenges For Arterial-phase Imagingmentioning
confidence: 99%